Aspired communities - Posio Pilvi (Turun yliopisto, 2025)
I argue in this thesis that we can understand the various ways in which community is ontologized as a tangible, affective and compelling social reality through the analytical lens of the future orientation of collective aspiring. The social and material lives of the residents in the disaster-stricken Tohoku region of northeast Japan were drastically altered after the Great East Japan Earthquake and the tsunami on March 11 in 2011. Based on eight months of ethnographic fieldwork in 2014–2015 in the town of Yamamoto, I seek to understand in this PhD thesis how the local communities were recovering during the still-ongoing reconstruction then. The main objective of this thesis is to offer analytical tools to explore how people come to interpret, experience and feel their social existence as community.
I understand community in this research as embodied, materially grounded yet symbolical and discursive by drawing from the practice theory approach. The definition of community has long been debated, romanticized and nostalgized. Instead of as a particular grouping or identity, I analyze community as a process of mutually constitutive enacting and envisioning in social practices. I explore this process in light of the teleological character of human activity that is based on a constant reinterpretation of the past and a striving towards the future in the present. I argue that the various forms of sociality that are interpreted, experienced and felt as community can be understood through the future orientation of a collective aspiring of desired futures as shared objectives. As such, community is not a result but the process of collective aspiring in itself that I have divided into action-oriented pursuing and affectively charged yearning.
The ethnographic analysis of collective aspiring illustrates how multiple, ambiguous, overlapping and even conflicting experiences and interpretations of community emerged in post-disaster Yamamoto. My findings elaborate the community concept by highlighting the role of temporality and the future particularly in social life. This suggests that disaster recovery can be perceived as the process of restoring the capability to envision and to enact the future in and of a place, both individually and collectively. I also highlight the sense of agency in social practices, the felt, embodied and social security and the role of spatiality in collective aspiring.